Parameter Identification for Primary-Side Control of Inductive Wireless Power Transfer Systems: A Review - Mwangi Andrew Ngini; Chanh-Tin Truong; Sung-Jin Choi (IEEE Access)
Wireless power transfer (WPT) is an innovative technology that allows for seamless delivery of electrical energy from a power source to an electrical load without any physical connectors. Primary-side parameter identification, an aspect of primary-side control in WPT systems, enables the monitoring of system parameters without the conventional need for any secondary-side feedback signal. By accurately identifying key system parameters such as coupling or load conditions, the primary-side controller mechanisms can then adjust the operating conditions to maintain optimal power transfer efficiency and ensure reliable operation across varying conditions and energy coupler misalignments. This approach reduces complexity and minimizes the need for additional communication links between the primary-side and the secondary-side hence reduces cost of the system. In literature, numerous techniques for parameter identification along with primary-side control methods have been proposed. However, based on our gathered information, a review work regarding primary-side control techniques applying parameter identification for anti-misalignment and load variation has not been published yet. Therefore, this paper presents a comprehensive review regarding existing techniques in detail to provide an understanding of their operation and classification, investigating their pros and cons contributions to the WPT system.